2003
DOI: 10.5858/2003-127-854-pacmia
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic Acinar Cell Metaplasia in Autoimmune Gastritis

Abstract: Objective.—To determine the frequency and significance of pancreatic acinar cells in the gastric oxyntic mucosa. Design.—One hundred gastric oxyntic mucosal biopsy specimens from patients with chronic active gastritis (n = 30), multifocal atrophic gastritis (n = 15), autoimmune gastritis (n = 18), and normal gastric oxyntic mucosa (n = 37) were evaluated for the presence of pancreatic acinar cells. Formalin-fixed, paraffin-embedded tissues were stained with hematoxylin-eosin, and those positive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(5 citation statements)
references
References 9 publications
0
4
1
Order By: Relevance
“…Omeprazole was reported to cause PACM after six months of treatment in rats [17]. In humans, PACM is often observed in patients with autoimmune gastritis [3]. Hypergastrinemia is a shared feature between the oral administration of proton pump inhibitors and autoimmune gastritis; however, we did not nd a relationship between hypergastrinemia and PACM in patients with H. pylori gastritis in the present study.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…Omeprazole was reported to cause PACM after six months of treatment in rats [17]. In humans, PACM is often observed in patients with autoimmune gastritis [3]. Hypergastrinemia is a shared feature between the oral administration of proton pump inhibitors and autoimmune gastritis; however, we did not nd a relationship between hypergastrinemia and PACM in patients with H. pylori gastritis in the present study.…”
Section: Discussioncontrasting
confidence: 65%
“…Pancreatic acinar cell metaplasia (PACM), which is a rare nding in gastric mucosa (1), comprises clusters of pancreatic acinar cell-like cells that are mainly located in the gastric lamina propria [1]. PACM has been observed in the esophagogastric junction of patients with Barrett's esophagus and in the greater curvature of the gastric corpus in patients with autoimmune gastritis [2,3]. Unlike heterotopic pancreas, PACM lacks pancreatic ducts and islets of Langerhans [1,4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Other report showed that omeprazole was reported to cause PACM after six months of treatment in rats [ 18 ]. In humans, PACM is often observed in patients with autoimmune gastritis [ 3 ]. Hypergastrinemia is a shared feature between the oral administration of PPI and autoimmune gastritis; however, we did not find a relationship between hypergastrinemia and PACM in patients with H. pylori gastritis in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Pancreatic acinar cell metaplasia (PACM), which is a rare finding in gastric mucosa, comprises clusters of pancreatic acinar cell-like cells that are mainly located in the gastric lamina propria [ 1 ]. PACM has been observed in the esophagogastric junction of patients with Barrett’s esophagus and in the greater curvature of the gastric corpus in patients with autoimmune gastritis [ 2 , 3 ]. Unlike heterotopic pancreas, PACM lacks pancreatic ducts and islets of Langerhans [ 1 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the stomach, pancreatic tissue can be found in two different forms: as HP or as gastric pancreatic metaplasia characterised by nests, lobes or isolated pancreatic cells in gastric mucosa. The latter has been related with autoimmune gastritis [25,26,27].…”
Section: Clinical Casementioning
confidence: 99%